Flexible Terahertz Metamaterial Biosensor for Ultra-Sensitive Detection of Hepatitis B Viral DNA Based on the Metal-Enhanced Sandwich Assay - Li, Yumin; Wang, Xiaojing; Liu, Yu; Jin, Weidong; Tian, Huiyan; Xie, Fengxin; Xia, Ke; Zhang, Xiuming; Fu, Weiling; Zhang, Yang (Frontiers in Bioengineering and Biotechnology, 2022)
The high sensitivity and specificity of terahertz (THz) biosensing are both promising and challenging in DNA sample detection. This study produced and refined a flexible THz MM biosensor for ultrasensitive detection of HBV in clinical serum samples based on a gold magnetic nanoparticle-mediated rolling circle amplification (GMNPs@RCA) sandwich assay under isothermal conditions. Typically, solid-phase RCA reactions mediated by circular padlock probes (PLPs) are triggered under isothermal conditions in the presence of HBV DNA, resulting in long single-stranded DNA (ssDNA) with high fidelity and specificity. Then, the resultant ssDNA was conjugated with detection probes (DPs) immobilized on gold nanoparticles (DP@AuNPs) to form GMNPs-RCA-AuNPs sandwich complexes. The HBV DNA concentrations were quantified by introducing GMNPs-RCA-AuNPs complexes into the metasurface of a flexible THz metamaterial-based biosensor chip and resulting in a red shift of the resonance peak of the THz metamaterials. This biosensor can lead to highly specific and sensitive detection with one-base mismatch discrimination and a limit of detection (LOD) down to 1.27E + 02 IU/ml of HBV DNA from clinical serum samples. The HBV DNA concentration was linearly correlated with the frequency shift of the THz metamaterials within the range of 1.27E + 02∼1.27E + 07 IU/ml, illustrating the applicability and accuracy of our assay in real clinical samples. This strategy constitutes a promising THz sensing method to identify virus DNA. In the future, it is hoped it can assist with pathogen identification and clinical diagnosis.